Implementasi Supervisi Akademik Kepala Madrasah di Madrasah Tsanawiyah Al-Wathoniyah 1A Duren Sawit Jakarta Timur pada Masa Pandemi Covid 19 - Alhan, Khusni (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2024)
This study aims to see how the implementation of academic supervision of headmaster during the Covid 19 pandemic. This research was conducted using qualitative methods with the type of phenomenological research. The research was conducted at MTs Al-Wathoniyah 1A Duren Sawit, Academic Year 2020-2021. Data collection was carried out by interview, observation and documentation. The subjects of this study were the headmster, the deputy head of the madrasah in the field of curriculum, and teachers in the field of study. The implementation of the academic supervision of headmaster is carried out in three cycles, namely cycle 1 in the form of a contract, cycle 2 in the form of implementation, and cycle 3 in the form of strengthening. The results showed that the implementation of academic supervision of headmaster during the Covid 19 pandemic was going well. Although the learning uses a weekly class shift system, it does not reduce the enthusiasm of the headmaster to continue to improve the quality of the teaching and learning process at MTs Al-Wathoniyah 1A Duren Sawit. Teaching and learning activities at MTs Al-Wathoniyah 1A Duren Sawit are conducted face-to-face with a system of alternating classes every week. MTs Al-Wathoniyah 1A Duren Sawit is in the green zone so that it was allowed by the Covid 19 task force team in North Labuhanbatu Regency to carry out face to-face teaching and learning activities